Sn Isotopic Values in Ten Geological Reference Materials by Double‐Spike MC‐ICP‐MS. Issue 3 (12th July 2022) - Wang, Zhao‐Yang; Luo, Zhen‐Yu; Zhang, Le; Liu, Jun‐Jie; Li, Jie
Abstract : The tin mass fraction and the δ 120/118 Sn relative to NIST SRM 3161a were measured for ten geological reference materials among which the Sn isotopic values of W‐2a, JA‐2, JG‐2, G‐2, GBW07316, NOD‐A‐1 and SGR‐1 are reported for the first time. The sample preparation procedure implemented in this study was based on acid digestion and matrix separation by two‐stage chromatographic using AG‐MP‐1 and TRU‐Spec resin. Isotopic measurements were carried out by multi‐collector inductively coupled plasma‐mass spectrometry (MC‐ICP‐MS), using a 117 Sn– 119 Sn double‐spike technique to correct for the instrumental mass fractionation effects. The overall precision of this method is estimated to be ± 0.03‰ (2 s, n  = 81) and ± 0.07‰ (2 s, n  = 6) for the NIST SRM 3161a and a geological reference material BHVO‐2, respectively. Abstract : Key Points Two‐stage chromatographic separation using AG MP‐1 and TRU‐Spec resins was used to separate Sn from geological materials. The double‐spike technique was employed to correct for instrumental mass fractionation. δ 120/118 Sn values of ten reference materials are reported with precisions better than ± 0.07‰.